Systematic study of genus Boesenbergia Kuntze in Sarawak - Mas Izzaty, Mazlan (Universiti Malaysia Sarawak(UNIMAS), 2016)
The genus Boesenbergia is a small group of ginger species belonging to the family Zingiberaceae. Twenty-two species were found in Sarawak. Some of the species B. stenophylla R.M. Smith produced a great medicinal value which can treat headaches or stomach – ache disorders. Systematic study was done on a particular species of Boesenbergia at a certain locations. Herbarium specimens also were used in addition to freshly collected specimens for systematic study of genus Boesenbergia. There had some gap of information between previous and recent information, so this study was expected to provide an additional taxonomic and basic data for the researcher to further their studies on this genus. The objectives of this study were to study the distribution and habitat of the genus Boesenbergia in Sarawak, to compare the morphological characteristics between each species of Boesenbergia and lastly to compare the leaf anatomy and pollen characteristics between each species of Boesenbergia recorded in Sarawak. A total of 22 species including a new species (B. atropurpurea Mas Izzaty., M, Tawan, C.S., Meekiong, K.) were recognized within the genus Boesenbergia found in 30 location that had been visited in Sarawak. Fourteen species of Boesenbergia were identified endemic to Sarawak. Miri division had the highest diversity with 21 species recorded followed by Kapit division eight species, Kuching division six species and also Limbang division with five species recorded. For habitat, 21 species were recorded in the mixed dipterocarp forest, two species in the tropical heath forest, five species in riverine forest, nine species in lower and upper montane forest, nine species in limestone forest and three species were found in secondary forest. The morphological characters of all the species identified were thoroughly examined. The micromorphology of the leaves, bracteole, labellum, stamens, stigmas and anther – crest being investigated for the first time. The leaf anatomical characters, including the epidermal cell of leaves, stomata and petioles were studied. From this investigation, the descriptions of the species in the genus were given. Identification keys and synonyms of the species were also included.